2017
DOI: 10.1093/nar/gkx466
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bacterial gene rearrangement: SprA-catalyzed precise DNA recombination and its directionality control by SprB ensure the gene rearrangement and stable expression of spsM during sporulation in Bacillus subtilis

Abstract: A sporulation-specific gene, spsM, is disrupted by an active prophage, SPβ, in the genome of Bacillus subtilis. SPβ excision is required for two critical steps: the onset of the phage lytic cycle and the reconstitution of the spsM-coding frame during sporulation. Our in vitro study demonstrated that SprA, a serine-type integrase, catalyzed integration and excision reactions between attP of SPβ and attB within spsM, while SprB, a recombination directionality factor, was necessary only for the excision between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 68 publications
(91 reference statements)
3
53
0
Order By: Relevance
“…Rhamnose is not the sole carbohydrate present on the spore surface (Wunschel et al , ). In B. subtilis , another contributor to spore polysaccharide synthesis is the spsM gene, which is reconstituted specifically through a rearrangement of the mother cell genome during late sporulation (Abe et al , ; ), and two σ K ‐controlled paralogs of spsI , yfnH and ytdA , although the identity of the sugars produced remains unclear (Arrieta‐Ortiz et al , ). It has also been suggested that the presence of a mucous layer surrounding spores in certain strains of B. subtilis influenced hydrophobicity and adhesion properties (Faille et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnose is not the sole carbohydrate present on the spore surface (Wunschel et al , ). In B. subtilis , another contributor to spore polysaccharide synthesis is the spsM gene, which is reconstituted specifically through a rearrangement of the mother cell genome during late sporulation (Abe et al , ; ), and two σ K ‐controlled paralogs of spsI , yfnH and ytdA , although the identity of the sugars produced remains unclear (Arrieta‐Ortiz et al , ). It has also been suggested that the presence of a mucous layer surrounding spores in certain strains of B. subtilis influenced hydrophobicity and adhesion properties (Faille et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, such cases need not inactivate the gene; thus, simply detecting that an IGE has invaded a CDS is not sufficient to show that gene function has been inactivated. More rarely, IGEs are known to inactivate genes within conserved peptideencoding regions, in two situations: 1) accidental targeting of the gene by a promiscuous integrase or by an off-target event from a site-specific integrase, or 2) regulatory gene inactivation as described at comK, sigK, spsM, mutL, gerE, mlrA, hlb, nifD, fdxN and hupL (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). We devised a stringent test for gene inactivation, namely, Pfam domain disruption, by any non-tRNA IGE, comparing top Pfam scores for possible peptides encoded in the attB region to those for the attLR regions (Table 1).…”
Section: Islander False Positives Highlight the Cohesion Of The Integmentioning
confidence: 99%
“…However certain IGEs are known to control gene activity, inactivating the target CDS upon integration and reactivating it upon excision (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This regulated gene integrity (RGI) can occur irreversibly in the development of nonreproducing cells of multicellular bacteria, where integrases catalyze specific IGE deletions in the chromosome that restore the sigK or spsM genes in spore mother cells (5,10,12), or the nifD, hupL, or fdxN genes in cyanobacterial heterocysts (6,8,9). RGI can also occur reversibly, as at the Listeria comK or the Streptococcus mutL genes (11,13), where excision of the IGE circle temporarily alters gene expression until the circle re-integrates (7).…”
Section: Introductionmentioning
confidence: 99%
“…In strain 168, the skin element, for example, is removed in the mother cell during the sporulation process, generating the sporulation‐specific sigma factor K (Krogh et al ., 1996). In the same way, the spsM gene is interrupted by bacteriophage SPbeta which is excised during the sporulation process using two phage‐encoded proteins, SprA and SprB (Abe et al ., 2017). This is now recognized as a new role of lysogeny, named ‘active lysogeny’, that provides yet another account for the presence of bacteriophages within bacteria (Feiner et al ., 2015), with B. subtilis as a paradigmatic example.…”
Section: Bacillus Subtilis In 2017mentioning
confidence: 99%